Surface functionalisation of Microfibrillated Cellulose (MFC) of cocoa pod husk with Ƴ-Methacryloxypropyltrimethoxysilane (MPS) - Syed Putra, Sharifah Shahira; Jimat, Dzun Noraini; Wan Nawawi, Wan Mohd Fazli; Sulaiman, Sarina; Jamal, Parveen; Ahmad Nor, Yusilawati (Elsevier Doyma, 2018)
Significant growing on environmental awareness has led researchers to study the surface functionalisation of cellulose nanofiber using natural renewable resources. This study aims to improve the percentage swelling of microfibrillated cellulose (MFC) of cocoa pod husks, crops-by product with Ƴ- methacryloxypropyltrimethoxysilane (MPS). Investigation on the effect of cocoa pod husk (CPH) microfibrillated cellulose (MFC-CPH) amount, MPS amount, MPS concentration and the reaction time to the percentage of swelling property of MFC-CPH treated with MPS was carried out. Composition amount of CPH -MFC, MPS, MPS concentration and the reaction time were varied from range of 0.5-6 gram, 1-9 mL, 5-15 w/w % and 2-24 hours respectively. Based on evaluation of percentage swelling obtained, it showed that the surface hydrophobicity of MFC-CPH treated with MPS could be increased due to the chemical bonds interaction that formed during silane treatment. The lowest percentage swelling of treated MFC-CPH-MPS is 14.96 % and the highest is 94.87 %. The untreated and treated MFC-CPH were then observed using fourier transform infrared (FT-IR) and field emission scanning electron microscopy (FESEM) for any change of structural and morphology. FT-IR results shows that there is reduction of OH groups in cellulose and addition of Si groups after silane treatment. There is also a change on the surface of MFC-CPH fibers after silane treatment as MFC-CPH fibers surface become rough due to deposited of MPS on MFC-CPH fibers.